Efficacy of biofungicide Bacillus subtilis Ch-13 in the suppression of Hypomyces odoratus (cobweb disease) in a large-scale white button mushroom production (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2026)
More frequent application of the biofungicide Bacillus subtilis Ch-13 enhanced its efficacy against natural infestation of Hypomyces odoratus (cobweb disease) in white button mushrooms (Agaricus bisporus), as well as its positive impact on mushroom production. In two different application procedures, strain B. subtilis Ch-13 was used at a final concentration of 60 ml per m2 of casing layer (1 × 108 CFU ml-1). In comparison to the low efficacy of the fungicide prochloraz (53%), optimal efficacy of B. subtilis Ch-13 in the suppression of H. odoratus was recorded. Substantially higher efficacy of this biofungicide in cobweb disease control was achieved when it was applied in three split doses (42%), rather than two (30%), in the large-scale production of white button mushrooms. The greatest improvement in white button mushroom production, in comparison to the untreated control, was achieved when B. subtilis Ch-13 was applied in three split doses (biological efficiency, BE=15%), rather than two (BE=7%). For suppression of the mycopathogen H. odoratus on white button mushrooms, this study supports the application of the biofungicide B. subtilis Ch-13 in three split doses of 30 + 15 + 15 ml m-2 on the second day after casing, two weeks after casing, and after the first fruiting flush, respectively.
Keywords: edible mushrooms; biocontrol agent; disease control